Determination of the muon charge sign with the dipolar spectrometers of the OPERA experiment. (25th July 2016) - Agafonova, N.; Aleksandrov, A.; Anokhina, A.; Aoki, S.; Ariga, A.; Ariga, T.; Bender, D.; Bertolin, A.; Bozza, C.; Brugnera, R.; Buonaura, A.; Buontempo, S.; et al.
Abstract: The OPERA long-baseline neutrino-oscillation experiment has observed the direct appearance of ντ in the CNGS νμ beam. Two large muon magnetic spectrometers are used to identify muons produced in the τ leptonic decay and in νμ CC interactions by measuring their charge and momentum. Besides the kinematic analysis of the τ decays, background resulting from the decay of charmed particles produced in νμ CC interactions is reduced by efficiently identifying the muon track. A new method for the charge sign determination has been applied, via a weighted angular matching of the straight track-segments reconstructed in the different parts of the dipole magnets. Results obtained for Monte Carlo and real data are presented. Comparison with a method where no matching is used shows a significant reduction of up to 40% of the fraction of wrongly determined charges.